PWE-007 Liver Disease in Patients with Inflammatory Bowel Disease (IBD): Causes, Presentations and Outcomes. (17th August 2016) - Warner, BD; Basra, M; Anderson, S; Irving, P; Sanderson, J
Abstract : Introduction: Although deranged liver function tests(LFTs) are seen in around 1/3 of patients with IBD at some point during the course of their disease, there is a lack of clarity over how this should be investigated and managed. Methods: IBD patients attending clinic between September 2014 and December 2015 were analysed for previously elevated alanine transferase((ALT) defined as >56 IU/L). Analyses, where there were derangement of gamma glutamyl transferase and alkaline phosphatase (ALP) only, were not performed. Data was collected for disease activity, medication, time to ALT normalisation(in months) and ALP. Results: Data on 236 patients with elevated ALT were collected(50.4% male, mean age 40 years(range 16 to 83)). 64% had Crohn's disease(CD). 61% had active disease at the time of elevated ALT. Liver injury was predominantly hepatitic(mean ALT:ALP ratio 1.52). Mean ALT was 159 (maximum 1980). Of the patients with PSC, 81% had ulcerative colitis(UC) of whom 75% had pancolitis. The mean ALT:ALP ratio was 0.47 and therefore cholestatic(SD 0.29). Overall, 70% of patients had an ALT which normalised completely(mean of 2.4 months(SD 2.7)). 37% were due to thiopurines and 35% due to disease flares. 6% were other drug related (methotrexate in 8 cases, mesalazines in 2). Where ALT did not normalise, 21% were diagnosed with a chronic liver disease. 2/3 of thiopurine-induced hepatotoxicity were associated with hypermethylation(Methylmercaptopurine to thioguanine nucleotide ratio >11) and mean ALT:ALP was 1.74 and therefore hepatitic(range 0.15–11.57, SD 1.67). Median time for normalisation of thiopurine-induced hepatotoxicity was 2 months(SD 3.9) where as it was 0.5 months(SD 15.5) due to flares. Conclusion: Liver disease in IBD is common but rarely severe. Thiopurines are the commonest cause. Liver injury associated with active disease is also common. ALT normalised completely in over 95% of drug related cases. Where deranged LFTs continue for over 2 months, then a liver screen is indicated to exclude a chronic liver disease. Where liver derangement is cholestatic and the patient has UC, investigations should be carried out to exclude PSC. Disclosure of Interest: None Declared